GaAs(001): Surface Structure and Optical Properties - Schmidt, Wolf Gero; Bechstedt, F.; Fleischer, K.; Cobet, C.; Esser, N.; Richter, W.; Bernholc, J.; Onida, G. (physica status solidi (a))

Towards a Complete Many-Body Description: Optical Response of Real Surfaces - Bechstedt, F.; Schmidt, Wolf Gero; Hahn, P.H. (physica status solidi (a))

Theory for Modeling the Optical Properties of Surfaces - Onida, G.; Schmidt, Wolf Gero; Pulci, O.; Palummo, M.; Marini, A.; Hogan, C.; Del Sole, R. (physica status solidi (a))

X-ray diffraction analysis of the gallium-rich surface of GaAs(001) - Paget, D.; Garreau, Y.; Sauvage, M.; Chiaradia, P.; Pinchaux, R.; Schmidt, Wolf Gero (Physical Review B)

First-principles study of InP and GaP(001) surfaces - Pulci, O.; Lüdge, K.; Vogt, P.; Esser, N.; Schmidt, Wolf Gero; Richter, W.; Bechstedt, F. (Computational Materials Science)

On the origin of resonance features in reflectance difference data of silicon - Hingerl, K; Balderas-Navarro, R.E; Bonanni, A; Tichopadek, P; Schmidt, Wolf (Applied Surface Science)

Terrace and step contributions to the optical anisotropy of Si(001) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Physical Review B)

Optical Anisotropy of theSiC(001)-(3×2)Surface: Evidence for the Two-Adlayer Asymmetric-Dimer Model - Lu, Wenchang; Schmidt, Wolf Gero; Briggs, E. L.; Bernholc, J. (Physical Review Letters)

Atomic structure and optical anisotropy of III–V(001) surfaces - Esser, N.; Schmidt, Wolf Gero; Cobet, C.; Fleischer, K.; Shkrebtii, A. I.; Fimland, B. O.; Richter, W. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Structure and Energetics of P-rich GaP(001) Surfaces - Pulci, O.; Schmidt, Wolf Gero; Bechstedt, F. (physica status solidi (a))

On the origin of resonance features in reflectance difference data of silicon - Hingerl, K; Balderas-Navarro, R.E; Bonanni, A; Tichopadek, P; Schmidt, Wolf Gero (Applied Surface Science)

Terrace and step contributions to the optical anisotropy of Si(001) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Physical Review B)

First-principles study of (2×1) and (2×2) phosphorus-rich InP(001) surfaces - Pulci, Olivia; Lüdge, Kathy; Schmidt, Wolf Gero; Bechstedt, F (Surface Science)

(001) Surfaces of GaP and InP: structural motifs, electronic states and optical signatures - Schmidt, Wolf Gero; Bernholc, J.; Bechstedt, F. (Applied Surface Science)

Angle Resolved Photoemission Spectroscopy of the InP(001) surface - Frisch, A.M.; Vogt, P.; Visbeck, S.; Hannappel, Th.; Willig, F.; Braun, W.; Richter, W.; Bernholc, J.; Schmidt, Wolf Gero; Esser, N. (Applied Surface Science)

Surface phase diagram of (2×4) and (4×2) reconstructions of GaAs(001) - Schmidt, Wolf Gero; Mirbt, S.; Bechstedt, F. (Physical Review B)

Understanding reflectance anisotropy: Surface-state signatures and bulk-related features in the optical spectrum ofInP(001)(2×4) - Schmidt, Wolf Gero; Esser, N.; Frisch, A. M.; Vogt, P.; Bernholc, J.; Bechstedt, F.; Zorn, M.; Hannappel, Th.; Visbeck, S.; Willig, F.; Richter, W. (Physical Review B)

Understanding reflectance anisotropy: Surface-state signatures and bulk-related features - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Step-induced optical anisotropy of Si(111):H surfaces - Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

Large-Scale Applications of Real-Space Multigrid Methods to Surfaces, Nanotubes and Quantum Transport - Bernholc, J.; Briggs, E. L.; Bungaro, C.; Buongiorno Nardelli, M.; Fattebert, J. -L.; Rapcewicz, K.; Roland, C.; Schmidt, Wolf Gero; Zhao, Q. (Computer Simulation of Materials at Atomic Level)

Ab initio calculation of linear and nonlinear optical properties of semiconductor structures - Bechstedt, F.; Adolph, B.; Schmidt, Wolf Gero (Brazilian Journal of Physics)

SELF-ENERGY EFFECTS IN THE OPTICAL ANISOTROPY OF GaP(001) - Schmidt, Wolf Gero; FATTEBERT, J. L.; BERNHOLC, J.; BECHSTEDT, F. (Surface Review and Letters)
We calculate the reflectance anisotropy for GaP(001)(2×4) surfaces using a real-space multigrid method and ab initio pseudopotentials. Our results obtained within DFT-LDA show good qualitative agreement with recent experiments. This holds in particular for the stoichiometric trends. A strong negative anisotropy at low photon energies is linked to the formation of Ga–Ga bonds along the [110] direction. There are discrepancies, however, with respect to the line shape and the energetic positions of characteristic peaks. Substantial improvement is achieved by using a numerically efficient GW approach with approximations for local-field effects and dynamical screening. We find that the spectral features related to transitions between surface perturbed bulk wave functions are more strongly affected by self-energy corrections than anisotropies directly linked to surface electronic states.

Theoretical Aspects of the Optical Response of Semiconductor Surfaces - Bechstedt, F.; Pulci, O.; Schmidt, Wolf Gero (physica status solidi (a))

GaP(001) and InP(001): Reflectance anisotropy and surface geometry - Esser, N.; Schmidt, Wolf Gero; Bernholc, J.; Frisch, A. M.; Vogt, P.; Zorn, M.; Pristovsek, M.; Richter, W.; Bechstedt, F.; Hannappel, Th.; Visbeck, S. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

(2×4)GaP(001) surface: Atomic structure and optical anisotropy - Frisch, A. M.; Schmidt, Wolf Gero; Bernholc, J.; Pristovsek, M.; Esser, N.; Richter, W. (Physical Review B)

Structural fingerprints in the reflectance anisotropy spectra ofInP(001)(2×4)surfaces - Schmidt, Wolf Gero; Briggs, E. L.; Bernholc, J.; Bechstedt, F. (Physical Review B)

Reflectance Anisotropy of GaAs(100): Theory and Experiment - Shkrebtii, A. I.; Esser, N.; Richter, W.; Schmidt, Wolf Gero; Bechstedt, F.; Fimland, B. O.; Kley, A.; Del Sole, R. (Physical Review Letters)

Geometry and electronic structure of InP(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Atomic structure of InP(001)-(2×4): A dimer reconstruction - Schmidt, Wolf Gero; Bechstedt, F.; Esser, N.; Pristovsek, M.; Schultz, Ch.; Richter, W. (Physical Review B)

In-induced (4 × 2) reconstructions of GaAs(001) surfaces - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Applied Surface Science)

A High Resolution Investigation of the Anisotropic Electron-Positron Momentum Distribution in Diamond - Nilen, R.W.N.; Connell, S.H.; Britton, D.T.; Fischer, C.G.; Sendezera, E.J.; Schmidt, Wolf Gero; Sellschop, J.P.F.; Verwoerd, W.S. (Materials Science Forum)

(4×2) and (2×4) reconstructions of GaAs and InP(001) surfaces - Schmidt, Wolf Gero (Applied Physics A: Materials Science & Processing)

The anisotropic electron - positron momentum distribution in diamond - Nilen, R W N; Connell, S H; Britton, D T; Fischer, C G; Sendezera, E J; Schaaff, P; Schmidt, Wolf Gero; Sellschop, J P F; Verwoerd, W S (Journal of Physics: Condensed Matter)

As on InP(110) studied within density-functional theory - Grossner, U.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Chemisorption of arsenic on InP(110) - Großner, U.; Schmidt, Wolf Gero; Bechstedt, F.; Santos, P.V.; Koopmans, B.; Esser, N. (Surface Science)

Comparison of As-rich and Sb-terminated GaAs(100)(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Antimony-stabilized GaAs(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Electron-positron momentum density distribution in diamond - Nilen, R.W.N.; Connell, S.H.; Schmidt, Wolf Gero; Britton, D.T.; Verwoerd, W.S.; Sellschop, J.P.F.; Shrivastava, S. (Applied Surface Science)

Atomic Structure of the Sb-Stabilized GaAs(100)-(2×4) Surface - Esser, N.; Shkrebtii, A. I.; Resch-Esser, U.; Springer, C.; Richter, W.; Schmidt, Wolf Gero; Bechstedt, F.; Del Sole, R. (Physical Review Letters)

Geometry and electronic structure of GaAs(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Optical Properties of Ordered As Layers on InP(110) Surfaces - Santos, Paulo V.; Koopmans, B.; Esser, N.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Atomic structures of GaAs(100)-(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Adatoms and vacancies on the diamond(111) surface - Bechstedt, F; Schmidt, Wolf Gero; Scholze, A (Europhysics Letters (EPL))

Adsorption of group-V elements on III–V (1 1 0) surfaces - Schmidt, W (Surface Science Reports)

Annihilation of delocalized positrons: a comparison of diamond and silicon - Schmidt, Wolf Gero; Verwoerd, W.S (Physics Letters A)

Structure of the diamond (111) surface: Single-dangling-bond versus triple-dangling-bond face - Scholze, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Diamond (111) and (100) surface reconstructions - Scholze, A.; Schmidt, Wolf Gero; Bechstedt, F. (Thin Solid Films)

Phonons at III–V (110) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Srivastava, G.P. (Surface Science)

Dimerized, buckled, or ideal chains on the diamond (111)2 × 1 surface? - Schmidt, Wolf Gero; Scholze, A.; Bechstedt, F. (Surface Science)

Se-induced 3d core-level shifts of GaAs(110) - Käckell, Peter; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Applied Surface Science)

Diamond (111) and (100) surface: ab initio study of the atomic and electronic structure - Scholze, A.; Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Materials Science and Engineering: B)

Hydrogen interaction with Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Groenen, J.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Optical properties of Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

III-V(110) surface dynamics from anab initiofrozen-phonon approach - Schmidt, Wolf Gero; Bechstedt, F.; Srivastava, G. P. (Physical Review B)

Se/GaAs(110): energetics and structure - Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

Geometrical and electronic structure of the reconstructed diamond (100) surface - Kress, C.; Fiedler, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Exchange reactions versus adsorption geometries for Se/GaAs(110) - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Se/GaAs(110): Atomic and electronic structure - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Energetics and Structure of Ordered Sb Overlayers and Sb Clusters on GaAs(110) Probed by Ab Initio Calculations - Bechstedt, F; Schmidt, Wolf Gero; Wenzien, B (Europhysics Letters (EPL))

First principles calculations of interface phonons of an Epitaxial Sb monolayer on GaAs(110) and InP(110) - Schmidt, Wolf Gero; Srivastava, GP (Solid State Communications)

Coverage-dependent bonding of Sb on GaAs (110) - Schmidt, Wolf Gero; Wenzien, Bernd; Bechstedt, Friedhelm (Surface Science)

Chemisorption of antimony on GaAs(110) - Schmidt, Wolf Gero; Wenzien, B.; Bechstedt, F. (Physical Review B)

Chemisorption of aluminium on GaAs(110) - Schmidt, Wolf Gero; Srivastava, G P (Journal of Physics: Condensed Matter)

AB initio calculation of the atomic and electronic structure for Sb adsorbed on GaAs(110) - Schmidt, Wolf Gero; Wenzien, Bernd; Bechstedt, Friedhelm (Czechoslovak Journal of Physics)